Luescher, T.M., Webbstock, D. & Bhengu, N. (Eds.) (2020). Reflections of South African Student Leaders, 1994 to 2017. Cape Town, South Africa: African Minds. (Journal of Student Affairs in Africa, 2021)
The book, Reflections of South African Student Leaders, 1994 to 2017, edited by Thierry Luescher, Denyse Webbstock and Ntokozo Bhengu, presents an original perspective on the period before and during the university student protests of 2015 and 2016, not only as it is made up of student leaders' voices, but also in that it adopts a 'bottom up' approach where students themselves contextualise their own experiences. A lot has been written about the university managements' experience of this period - see for instance Jansen's As by Fire (2019) and Habib's Rebels and Rage (2018) - but this collection of student leaders' voices and the discussion of their reflections is a significant first.